Design in the face of uncertainty: prevention, preservation, and mitigation of coastal damage from storm surge and flooding - Gray, Allyssa (Kansas State University, 2020)
The climate is changing and there is an increase of hurricanes, flood events, and isolated storms. Storm surge and flooding have become a severe and recurring issue affecting Galveston Island, Texas. The impact of said events threatens the economy, culture, and ecology of the Island. The Gulf of Mexico and Galveston Bay are interwoven in the social and economic framework of Galveston Island. The purpose of the report is a proposed master plan of Galveston Island, Texas that increases the Islands Resiliency to storm surge and flooding. The master plan is informed through a study of literature, precedent studies, interviews with city officials, and an assessment of the Island. The project addresses how hybrid-infrastructure principals may be applied to Galveston Island to reduce the impact of storm surge and flooding.
Keywords: Resiliency; Storm surge; Flooding; Coastal; Galveston, Texas